An Approach to Identify Human based upon Teeth Recognition using ANN (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Neural networks are highly being used in the dentistry field. The purpose of this paper was to visualize the state of the art of artificial intelligence in dental applications. Here, a model of teeth acknowledgment has been proposed to distinguish an individual and recover the subtleties of the individual. The person’s teeth image will be taken as input and it will be matched against the database of teeth images. Artificial Neural networks algorithm has been used to train and recognizing the person to whom the teeth image belongs to. When person visit to dental hospital for the first-time doctor will capture ten images of his teeth and creates a new user in model to store his name, medical related issues, age etc. For further visiting he should just show his teeth to get his details. Testing Set accuracy is maintained to be 81.69 percent with the test set.